Insecticidal and Repellent Activities of Essential Oils from Seed and Root of Celery (Apium graveolens L.) Against Three Stored Product Insects. Issue 5 (3rd September 2021) - Qi, Xiao-jie; Feng, Yi-Xi; Pang, Xue; Du, Shu-Shan
Abstract: To exploit botanical insecticides and decrease the damage to crops by stored insects, we analyzed the chemical composition of essential oils derived from celery ( Apium graveolens L. ) seed and root. Repellent and insecticidal activity of obtained essential oils and components derived from celery seed and root against Tribolium castaneum (Coleoptera: Tenebrionidae), Lasioderma serricorne (Coleoptera: Anobiidae), and Liposcelis bostrychophila (Psocoptera: Liposcelididae) were evaluated. A total of fourteen and twelve components were respectively identified from the celery seed and root essential oil. D-limonene (79.3 %) and myristicin (47.3 %) were respectively the dominant components of seed and root essential oil. The root essential oil, D-limonene, and myristicin exhibited strong repellent activity (over 80 %) against T. castaneum at a concentration of 78.63 and 15.83 nL/cm 2 after 2 h exposure. The seed essential oil, root essential oil, D- limonene, and myristicin showed contact toxicity against T. castaneum, L. serricorne, and L. bostrychophila with LD50 values of 16.15, 18.74, 14.57, and 36.46 μg/adult; 16.01, 74.78, 13.91, and 22.15 μg/adult; 199.56, 208.91, 810.85, and 29.71 μg/cm 2, respectively. Seed essential oil and D-limonene showed stronger fumigant toxicity against T. castaneum, L. serricorne, and L. bostrychophila with LD50 values of 18.41 and 9.25 μg/ adult; 86.98 and 14.32 μg/adult; 36.58 and 18.39 μg/cm 2, respectively. These findings suggested celery could be used as a botanical insecticide for insect management.